KONSEP JIHAD MENURUT M. QURAISH SHIHAB DALAM TAFSIR AL-MISHBÃH DAN KAITANNYA DENGAN MATERI PENDIDIKAN AGAMA ISLAM - Ngadhimah, Mambaul; Huda, Ridhol (IAIN Ponorogo, 2015)
Abstract: An article which discusses jihad that originates in al-Mishba>h is the interpretation of al-Qurâan by M. Quraish Shihab. This becomes important because of the emergence of various typologies of jihad. Jihad with the typology of liberal group that sought to remove the Islamic law affecting on the implementation of jihad is just to fight the passions or demons and negate the other meanings of jihad. Jihad with the typology of radical group that declared war on the world and all unbelievers should be fought because of infidelity affects the meaning of jihad that only deals with war. Jihad with the typology of the moderate group believes that jihad in accordance with all forms of the reality of human life can be done by everyone in any way according to their ability and circumstances.Â Ø±ÙÙØ¸Ù Ø§Ù ÙÙ Ø¹ÙØ¶ÙÙÙ Ø§ ÙØ§Ù .Ø¨Ø§ÙØ´ Ø´ÙØ±Ù Ø°Ø§ØªØ³ÙØ£Ù â ØØ§Ø¨ØµÙÙ Ø§ â ÙØ±Ø³ÙØª ÙÙ â Ø¯Ø§ÙÙØ¬Ø§ â Ø¹ÙØ¶ÙÙ Ø©ÙØ§ÙÙÙ Ø§ ÙØ°Ù ØªØ³Ø±Ø¯Â Ø)ÙØ§ØªÙÙØ§ ÙÙØ¹Ø¨Ù ( Ø¯Ø§ÙÙØ¬Ø§ Ø©ÙØ¹ÙØ±Ø´Ù ØØ³Ù Ø§ÙÙÙØ§Ø Ù ÙÙØ£ ÙÙÙÙØ§Ø¨Ø±ÙÙØ§ Ø¯ÙØ¹ Ø¯Ø§ÙÙØ¬Ø§ Ù ÙÙÙÙ .Ø¯Ø§ÙÙØ¬Ø§ ÙÙ ÙØ§Ø¹Ù Ø©Ø¯Ø¹Â Ø¯Ø§ÙÙØ¬Ø§ ÙÙØ§Ø¹Ù ÙÙÙÙ ÙÙØ£ Ø¨ÙØ§Ø¨Ø¬ ØÙÙØ·Ø§ÙØ´ÙØ§ Ø©Ø§Ø¯Ø§Ø¹Ù Ù Ø³ÙÙÙØ§ Ø©Ø¯ÙØ§Ù Ø¬ ÙÙØ£ ÙÙØ¹ Ø¯Ø§ÙÙØ¬Ø§ Ø°ÙÙÙØª ÙÙØ¥ ÙÙ Ø¯Ø¤Ù Ø§Ø°ÙÙÂ ÙÙØ¥ ÙØ¯Ø¤Ù Ø§Ø°ÙÙ ØÙ ÙØ±ÙÙ Ø¨Ø¨Ø³Ø¨ Ø±Ø§ÙÙÙØ§Ù Ø§ÙÙØ¯ÙØ§ Ø©Ø¨Ø±Ø§Ù Ø ÙÙ ÙÙÙÙÙØµÙØ£Ø§ ÙÙÙÙ Ø±Ø·ØªÙÙ Ø§ ÙØ§Ø±Ù Ø§Ù Ù Ø¯Ø§ÙÙØ¬Ø§Ù .ÙØ±Ø®ÙØ£Ø§Â Ø©Ø§ÙØ Ø¹ÙØ§Ù ÙØ§ÙØ´Ø£ Ø¹ÙÙ Ø¨Ø¬ Ø¨Ø³Ø§ÙÙ ÙÙØ£ ÙÙÙ ÙØ·Ø³ÙÙØ§ Ø¯ÙØ¹ Ø¯Ø§ÙÙØ¬Ø§ Ù ÙÙÙÙ Ø§Ù Ø£ .Ø¨Ø³ØÙ ÙØ§ØªÙÙØ§ ÙÙØ¹Ø¨Ù Ø¯Ø§ÙÙØ¬Ø§ Ù ÙÙÂ .ÙÙÙØ±Ø¸Ù ÙØªÙØ§Ø· Ø¨Ø³Ø ÙÙØ¹ ØªÙØ§Ù Ø©ÙÙØ±Ø· ÙØ£Ø¨Ù ÙØ¡Ø§Ø¯Ø£ Ø¯Ø±Ù ÙÙÙ ÙÙÙÙ Ù ØØ³Ø§ÙÙØ§